Cross-cultural analysis of national attitudes towards legal contracts - Balabukha, K. V.; Балабукша, К. В. (Одеса : Фенікс, 2014)
It can hardly be doubted that the facts mentioned above gains vital im-portance today, particularly for lawyers who assist developing of contractual relationships on international arena.
Balabukha, K. V. Cross-cultural analysis of national attitudes towards legal contracts / K. V. Balabukha // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 600-602.
Keywords: cross-cultural analysis of national attitudes towards legal contracts; кросс-культурный анализ национальных отношений по отношению к правовым договорам; крос-культурний аналіз національних відносин по відношенню до правових договорів